2017
DOI: 10.5539/jel.v6n2p155
|View full text |Cite
|
Sign up to set email alerts
|

Process-Oriented Measurement Using Electronic Tangibles

Abstract: This study evaluated a new measure for analyzing the process of children’s problem solving in a series completion task. This measure focused on a process that we entitled the Grouping of Answer Pieces (GAP) that was employed to provide information on problem representation and restructuring. The task was conducted using an electronic tangible interface, to allow for both natural manipulation of physical materials by the children, and computer monitoring of the process. The task was administered to 88 primary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…[30][31][32][33][34]. On the other hand, CA has been extensively used in schools [35][36][37][38], potentially due to its formative feature. Within this context and related to getting data on the students' learning process, Elliott/Resing/Beckmann [36] distinguish between dynamic testing and dynamic assessment, the former being of particular interest for academic researchers in psychology with a focus on the study of reasoning and problem-solving, and the latter for those having a practitioner orientation and tending to be particularly concerned with exploring the ways by which assessment data can inform educational practice.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33][34]. On the other hand, CA has been extensively used in schools [35][36][37][38], potentially due to its formative feature. Within this context and related to getting data on the students' learning process, Elliott/Resing/Beckmann [36] distinguish between dynamic testing and dynamic assessment, the former being of particular interest for academic researchers in psychology with a focus on the study of reasoning and problem-solving, and the latter for those having a practitioner orientation and tending to be particularly concerned with exploring the ways by which assessment data can inform educational practice.…”
Section: Introductionmentioning
confidence: 99%
“…To create a measure for the time taken for encoding, which would be less dependent on the overall speed of processing and completing items, the proportion of time taken for encoding was used. This indicator consisted of the encoding time, divided by the completion time (Kossowska & Nȩcka, 1994; Resing & Elliott, 2011; Veerbeek et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Information such as the processing time or the steps taken during task solving can be used to construct process indicators, which are said to reflect behavior or information processing (Goldhammer et al, 2017). Prior research has successfully uncovered process indicators in a variety of domains, and shown that process indicators indeed reflected individual differences in ability and could provide information beyond test (product) scores (e.g., Naumann & Goldhammer, 2017; Stadler et al, 2020; Veerbeek et al, 2017, 2019).…”
Section: Computerized Dynamic Testingmentioning
confidence: 99%
“…Traditional, or analogue, DA tasks or items vary dependant on the core domain being targeted or assessed. For example, inductive reasoning has been recognised as a key element of a child's pedagogical and cognitive development, assessable through activities such as seriation, categorisation, and analogies [8,90]. A common strategy is to use physical objects or artifacts-such as an assortment of wooden geometric-shaped blocks-to set a child challenges such as discerning where they match or differ and prompting them to order or move the objects to demonstrate their level of comprehension.…”
Section: Tangible User Interfaces (Tuis)mentioning
confidence: 99%